Treatment With Dimethyl Fumarate Attenuates Calcineurin Inhibitor-induced Nephrotoxicity. Issue 6 (June 2015) - Takasu, Chie; Vaziri, Nosratola D.; Li, Shiri; Robles, Lourdes; Vo, Kelly; Takasu, Mizuki; Pham, Christine; Liu, Shuman; Farzaneh, Seyed H.; Foster, Clarence E.; Stamos, Michael J.; Ichii, Hirohito
<x xml:space="preserve">Abstract</x> Background Cyclosporine A (CsA) is an immunosuppressive drug which has been widely used to prevent rejection after organ transplantation. However, its therapeutic use is limited by nephrotoxicity, in part mediated by oxidative stress. The present study aims to investigate the protective effects of dimethyl fumarate (DMF) on CsA-induced nephrotoxicity by enhancing the antioxidant defense system. Methods Male Sprague–Dawley rats were treated with CsA (n = 8, 20 mg/kg per day intraperitoneally) or CsA + DMF (n = 7, 50 mg/kg per day orally) for 28 days. Renal function, histopathology, malondialdehyde (MDA), myeloperoxidase levels, and antioxidant enzyme expression were determined. Results The DMF cotreatment ameliorated CsA-induced renal dysfunction as evidenced by significant decrease in serum creatinine (CsA 0.79 ± 0.02 mg/dL vs CsA + DMF 0.62 ± 0.04 mg/dL, P = 0.001) and urea (CsA 66.9 ± 0.4 mg/dL vs CsA + DMF 53.3 ± 2.6 mg/dl, P < 0.0001) levels, as well as improvement of creatinine clearance. Dimethyl fumarate also significantly decreased serum MDA and renal tissue MDA and myeloperoxidase contents. The protein expression of NAD(P)H quinone oxidoreductase-1, a major cellular antioxidant and detoxifying enzyme, was significantly enhanced by DMF administration in kidney. Conclusions Administration of DMF has a protective potential against CsA nephrotoxicity. The protection afforded by DMF is mediated in part through inhibiting oxidative stress and inflammation and enhancing the antioxidant capacity.